2021
DOI: 10.7554/elife.62592
|View full text |Cite
|
Sign up to set email alerts
|

A feedback loop between the androgen receptor and 6-phosphogluoconate dehydrogenase (6PGD) drives prostate cancer growth

Abstract: Alterations to the androgen receptor (AR) signalling axis and cellular metabolism are hallmarks of prostate cancer. This study provides insight into both hallmarks by uncovering a novel link between AR and the pentose phosphate pathway (PPP). Specifically, we identify 6-phosphogluoconate dehydrogenase (6PGD) as an androgen-regulated gene that is upregulated in prostate cancer. AR increased the expression of 6PGD indirectly via activation of sterol regulatory element binding protein 1 (SREBP1). Accordingly, los… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 60 publications
2
15
0
Order By: Relevance
“…Alternatively, small molecule inhibitor (enzalutamide) mediated pharmacological inhibition of AR signaling also results in a robust increase in MALAT1 expression in both LNCaP and VCaP cells, while no change was observed in 22RV1 cells ( Figure 5F) . In line with this, LNCaP cells (GSE152254) (54) treated with a lower concentration (1μM) of enzalutamide also show increased expression of MALAT1 as well as AR repressed genes, namely DDC and OPRK1 ( Supplemental Figure S4B). Conversely, a marked decrease in MALAT1 expression was noticed in VCaP cells stimulated with a sub-physiological concentration of synthetic androgen, R1881 (1 nM; GSE71797, (55) ( Supplemental Figure S4B).…”
Section: Resultssupporting
confidence: 61%
“…Alternatively, small molecule inhibitor (enzalutamide) mediated pharmacological inhibition of AR signaling also results in a robust increase in MALAT1 expression in both LNCaP and VCaP cells, while no change was observed in 22RV1 cells ( Figure 5F) . In line with this, LNCaP cells (GSE152254) (54) treated with a lower concentration (1μM) of enzalutamide also show increased expression of MALAT1 as well as AR repressed genes, namely DDC and OPRK1 ( Supplemental Figure S4B). Conversely, a marked decrease in MALAT1 expression was noticed in VCaP cells stimulated with a sub-physiological concentration of synthetic androgen, R1881 (1 nM; GSE71797, (55) ( Supplemental Figure S4B).…”
Section: Resultssupporting
confidence: 61%
“…A more comprehensive investigation of lactate metabolism in prostate cancer is clearly warranted. Finally, the pentose phosphate pathway (PPP) is a glucose catabolic pathway that appears to be important in prostate tumor growth in AR/SREBP/6PGD-dependent manner (45). However, whether PPP plays a significant role in prostate cancer by generating nucleotide precursor or sustaining the NADPH pool for lipogenesis and redox homeostasis is yet to be elucidated.…”
Section: Glucosementioning
confidence: 99%
“…The interlink with glycolysis is seen after isomerization of ribulose-5-phosphate (R5P) using transketolase and transaldolase. PPP is controlled by G6PDH wherein studies have indicated that this enzyme is increased in PCa [387][388][389][390][391]. G6PDH, NAPDH, and ribose synthesis were all upregulated in PCa through the action of AR signaling [343,388].…”
Section: Pentose Phosphate Pathwaymentioning
confidence: 99%